Decision making and action implementation: Evidence for an early visually triggered motor activation specific to potential actions. (16th May 2013) - Tandonnet, Christophe; Garry, Michael I.; Summers, Jeffery J.
Abstract To make a decision may rely on accumulating evidence in favor of one alternative until a threshold is reached. Sequential‐sampling models differ by the way of accumulating evidence and the link with action implementation. Here, we tested a model's prediction of an early action implementation specific to potential actions. We assessed the dynamics of action implementation in go/no‐go and between‐hand choice tasks by transcranial magnetic stimulation of the motor cortex (single‐ or paired‐pulse TMS; 3‐ms interstimulus interval). Prior to implementation of the selected action, the amplitude of the motor evoked potential first increased whatever the visual stimulus but only for the hand potentially involved in the to‐be‐produced action. These findings suggest that visual stimuli can trigger an early motor activation specific to potential actions, consistent with race‐like models with continuous transmission between decision making and action implementation.